Infection-mediated autoimmune movement disorders. (January 2018) - Cucca, Alberto; Migdadi, Hamzeh A.; Di Rocco, Alessandro
Abstract: Infectious diseases remain the most common cause of neurological disability in the world. A number of movement disorders can develop in adults and children in response to infections. These can occur in isolation or as part of a broader neurological illness, with movement abnormalities consequent to an encephalopathy or a broader brain dysfunction. While most infection-related movement disorders are direct consequences of an active infectious process affecting cerebral structures implied in the motor network, at times a delayed immune-mediated process in response to a previous infectious is responsible for the neurological dysfunction. This immunological response can occur as a consequence of a number of pathogens, and develop at variable times after the initial infection. The most common infection-mediated autoimmune movement disorders are chorea, which is especially common in children, and other hyperkinetic disorders, but Parkinsonism and other hypokinetic movement disorders may also occur.